Analisis Dampak Technological Deficiency terhadap Kinerja Karyawan pada UPK Syariah Tujuah Sarumpun Ampek Angkek Kabupaten Agam - Nur Kholilah; Yuwarman Mansur (ARZUSIN, 2026)
The decline in operational performance and membership at UPK Syariah Tujuah Sarumpun, Ampek Angkek Subdistrict, Agam Regency, indicates a problem suspected to be associated with technological deficiency. This study aimed to analyze the impact of technological limitations on employee performance. The study employed a qualitative approach with a descriptive design. Data were collected through observation, semistructured interviews, and documentation and were subsequently analyzed using an interactive model comprising data reduction, data display, and conclusion drawing. The results showed that limited hardware, the absence of integrated software, and the low digital competence of human resources caused administrative processes to remain manually conducted. These conditions adversely affected work-time efficiency, precision and accuracy, service quality, productivity, and employee professionalism. Technological limitations were also associated with a decline in financing realization from 102.20% in 2022 to 65.20% in 2024 and a decrease in the number of members. These findings confirm that technological deficiency negatively affects employee performance and organizational operational effectiveness. This study contributes to the development of research on technology utilization in Islamic microfinance institutions and provides practical implications regarding the need to upgrade technological infrastructure, provide integrated software, improve the digital competence of human resources, establish standard operating procedures, and improve service facilities.